Distinction of Justice and Fairness during Umar bin Abdul Azizs Reign - Meirison Meirison (AJIS: Academic Journal of Islamic Studies, 2019)
The figure of the caliph Umar bin Abdul Aziz was a leader who was able to carry out his religion, fulfill his mandate. He upholds justice which has often been ignored by his predecessors. He was able to challenge the current of tyranny which had become the culture of the ruler. He also remodeled the justice system, especially in the Mazalim (criminal) and civil fields. Not only humans who feel their justice but animals also get justice Umar bin Abdul Aziz. Renewal made by Umar bin Abdul Aziz in the field of justice, restore the rights of people who have been wronged, eradicate corruption, even he equates between worship and the implementation of hudud and qishas law. . This discussion was carried out by literature study by examining the books and analyzing them comparatively in the field of justice carried out before the time of Umar bin Abdul Aziz and what was reformed by Umar bin Abdul Aziz. Umar renewed the execution of the death sentence. The death penalty must be decided by the Caliph himself, fixing the prison administration. Umar bin Abdull Aziz began justice from himself and his family. Even animals feel justice Umar bin Abdul Aziz by limiting the cargo to be transported by camels and donkeys and may not hit the animal with iron.